(untitled) (Fiep Bulletin - online, 2014)
A key issue in physical education (PE) is the comparatively heterogeneous abilities and motor skills of students. In individual sports this issue can be addressed by methodical-didactic alternatives (e.g. internal differentiation) offering motor tasks of variable degrees of difficulty. In team sports internal differentiation is a particular challenge. Sports games do not only require equal teams for a balanced competition, but also individual differences in performance within the teams. Observations during PE demonstrate that in teams with highly variable playing skills strong players often dominate and play with each other. Thus, the inclusion of weaker players is limited and may result in loss of motivation. Experiences from practice show that participation of students with weaker playing skills can be improved through basic rule changes in competitive sports games. For example: • Separate the playing field into zones in which only specific players of both teams are allowed. • Include several goals or targets per team. • Mark areas from within it is forbidden to aim for the target or goal. • Restrict individual players’ movement with the ball. • Assign different players with varied ball handling and/or movement options. • Replace intensive body-involving forms of defence with symbolic defence actions.